How to treat acne in women with polycystic ovary syndrome (PCOS)? Review of the available literature - Ewelina Zygmunt; Hubert Wróblewski; Aleksandra Zimna; Dariusz Chojęta; Anna Kozłowska (Kazimierz Wielki University, 2022)
Acne vulgaris is one of the most common chronic skin diseases among people between 15 and 40 years of age.[i] It would seem that it is a typical disease of adolescence. However, it also very often affects adults. One of the most common causes of acne vulgaris in adult women is polycystic ovary syndrome (PCOS). The hyperandrogenism and metabolic disorders present in this syndrome may contribute to the formation of blackheads, pimples, and cysts on the face, chest and back. This article focuses on a review of current acne treatments associated with polycystic ovary syndrome.   [i] Stern RS. Medication and medical service utilization for acne 1995-1998. J Am Acad Dermatol 2000; 43: 1042-1048